Effects of tooth loss on brain structure: a voxel-based morphometry study. Issue 3 (July 2018) - Kobayashi, Takuya; Kubota, Masafumi; Takahashi, Toshiyuki; Nakasato, Ayaka; Nomura, Taro; Furuya, Junichi; Kondo, Hisatomo
Abstract: Purpose: One of the most prominent issues in a super-aging society is the rapid increase in dementia patients. Cross-sectional studies in dentistry have indicated that patients with dementia have worse oral health compared to healthy people. The purpose of this study was to clarify the influence of tooth loss on brain structure by comparing the volumes of gray matter (GM) and white matter (WM) between edentulous and dentulous subjects. Methods: Subjects were recruited from the Denture Clinic at Iwate Medical University Hospital Dental Center. Experiments were performed on edentulous (5 males, 8 females, 81.8 ± 1.24 years) and dentulous subjects (4 males, 7 females, 77.1 ± 4.25 years). Patients with dementia were excluded from this study. Brain volumes of GM and WM in edentulous and dentulous subjects were compared using intracranial volume, age, gender and history of hypertension as covariates. Analyzed brain areas were identified by transforming the Montreal Neurological Institute coordinate into the anatomical coordinate in edentulous subjects. Results: The analysis of WM structural images found no morphological differences between dentulous and edentulous subjects. However, significant atrophy of GM was observed in the hippocampus, caudate nucleus and temporal pole of the right hemisphere in edentulous subjects. Conclusions: The results of this study suggest that tooth loss was a causal factor for volume reduction in brain areas related to memory, learning and cognition.